Stem cell donor HLA typing improves CPRA in kidney allocation. Issue 1 (13th July 2020) - Kransdorf, Evan P.; Pando, Marcelo J.; Stewart, Darren; Lindblad, Kelsi; Bray, Robert; Murphey, Cathi; Kaur, Navchetan; Patel, Jignesh K.; Kim, Irene; Zhang, Xiaohai; Maiers, Martin; Kobashigawa, Jon A.; et al.
Abstract : The Organ Procurement and Transplantation Network (OPTN) Kidney Allocation System provides a priority to sensitized candidates based on the calculated panel reactive antibody (CPRA) value. The human leukocyte antigen (HLA) haplotype reference panel used for calculation of the CPRA by the United Network for Organ Sharing (UNOS), the OPTN contractor, has limitations. We derived a novel panel from the National Marrow Donor Program HLA haplotype data set and compared the accuracy of CPRA values generated with this panel (NMDP‐CPRA) to those generated from the UNOS panel (UNOS‐CPRA), using predicted and actual deceased donor kidney offers for a cohort of 24 282 candidates. The overall accuracy for kidney offers was similar using NMDP‐CPRA and UNOS‐CPRA. Accuracy was slightly higher for NMDP‐CPRA than UNOS‐CPRA for candidates in several highly sensitized CPRA categories, with deviations in linkage disequilibrium for Caucasians and the smaller size of the UNOS panel as contributing factors. HLA data derived from stem cell donors yields CPRA values that are comparable to those derived from deceased kidney donors while improving upon several problems with the current reference panel. Consideration should be given to using stem cell donors as the reference panel for calculation of CPRA to improve equity in kidney transplant allocation. Abstract : The authors derive a novel reference panel from the National Marrow Donor Program HLA haplotype dataset that exhibits similar accuracy to predict deceased donor kidney offers but slightly higher accuracy for candidates in several highly sensitized CPRA categories when compared to the UNOS panel.